Drug use among university students: meanings, motivations, and consequences in the context of higher education. - Landeros Díaz, Caroline; Muñoz Allendes, Catalina; Cabello Correa, Isabella; Chávez Osorio, Eduardo; Castro Andrade, Tiara (Relatos Journal, 2025)
For many students, university life means facing multiple challenges associated, for example, with academic performance, socialization, and the emotional demands of higher education. As a result, drug use emerges as a strategy for coping with or avoiding this situation in an adaptive manner. The aim of this research was to analyze the meanings, motivations, and consequences of drug use among higher education students at a private university in the Valparaíso Region, Chile. The methodological procedures were characterized by a descriptive qualitative design, where information was collected through a focus group with 10 students from different academic levels. The results show that drug use is the result of the interaction of multiple factors, including academic and family pressures, as well as the search for belonging and group validation. In this regard, there is recognition of the existence of a culture that normalizes drug use, perceiving it as a common and low-risk practice within the university context. However, based on the testimonies, negative consequences are identified, such as deterioration of academic performance, isolation, loss of meaningful activities, and weakening of support networks. The conclusion is that there is a need to strengthen institutional strategies for prevention, well-being, and comprehensive student support from a community and cultural perspective.
Keywords: Drug use; college students; higher education; academic pressure; normalization of use